Healing from heterosexism: A discovery-oriented task analysis of emotion-focused writing. - Collins, Kathleen M.; Levitt, Heidi M. (Journal of Gay & Lesbian Mental Health)
Background: Expressive writing exercises are associated with psychological benefits for LGBTQ + adults processing sexual minority stressors, but the processes through which this occurs remain unclear. Methods: A discovery-oriented task analysis was conducted on emotion-focused expressive writing responses about troubling heterosexist experiences. Eighteen cases were analyzed in total. Results: The analyses produced a four-stage model that describes the processes of resolving distress related to heterosexism. Conclusion: Results provide guidance for LGBTQ + affirmative mental health practitioners by naming the processes that clients may experience on the pathway to healing and identifying common obstacles to progress that clients may exhibit.